The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/zsc.12169
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the evolutionary relationships within the dog‐faced bats, genus Cynomops (Chiroptera: Molossidae)

Abstract: The low representativeness of the dog‐faced bats (genus Cynomops Thomas, ) in collections has constrained the study of the diversity and the evolutionary relationships within this genus. Taxonomic revisions of some taxa, in particular the large‐sized Cynomops abrasus (Temminck, ), are crucial for understanding the phylogeny of Cynomops. A total of four subspecies of C. abrasus have been described to date, all widespread in South America: C. a. mastivus (Thomas, ), C. a. brachymeles (Peters, 1865), C. a. cerast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 60 publications
(78 reference statements)
1
11
0
Order By: Relevance
“…(), Dávalos (), and Moras et al. (). Promops and Histiotus were represented in the original tree by one and two species, respectively, and did not require phylogenetic information to guide the replacements.…”
Section: Methodsmentioning
confidence: 99%
“…(), Dávalos (), and Moras et al. (). Promops and Histiotus were represented in the original tree by one and two species, respectively, and did not require phylogenetic information to guide the replacements.…”
Section: Methodsmentioning
confidence: 99%
“…Cynomops, Eumops, Molossops, Molossus, Neoplatymops and Nyctinomops represent six of the 16 genera of Molossidae recognized, and Eumops is the most diverse genus in the Neotropics (Medina et al, 2014). The complexity is even greater within the genus, since subspecies are recognized for many of its species (Eger, 1977;Timm and Genoways 2004;Simmons, 2005;Gregorin, 2009;Bartlett et al, 2013;Moras et al, 2016). Ryan (1991aRyan ( , 1991b was one of the first to study the external morphology of the glans in Molossidae species.…”
Section: Introductionmentioning
confidence: 99%
“…For African free-tailed bats, Lamb et al (2011) documented mean cyt- b genetic distances of 10.6% among four species of Mops , and a mean of 7.4% among seven species of Chaerephon . In the Neotropics, Moras et al (2016) found that cyt- b divergence averaged 9.7% among eight species of the genus Cynomops , and López-Baucells et al (2018) documented 12.1% mean sequence divergence among six species of Eumops in the mitochondrial COI locus. Differentiation between continental African Otomops species falls below the 5% threshold commonly found for species-level differences ( Bradley & Baker, 2001 ), but this is also the case for many other bat genera ( Velazco & Patterson, 2008 , 2013 ) and even for small, terrestrial species such as shrews ( Demos et al, 2016 , 2017 ).…”
Section: Discussionmentioning
confidence: 99%